Eupafolin nanoparticles protect HaCaT keratinocytes from particulate matter-induced inflammation and oxidative stress - Lin, Zih-Chan (Int J Nanomedicine, 2016)
Exposure to particulate matter (PM), a major form of air pollution, can induce oxidative stress and inflammation and may lead to many diseases in various organ systems including the skin. Eupafolin, a flavonoid compound derived from Phyla nodiflora, has been previously shown to exhibit various pharmacological activities, including antioxidant and anti-inflammatory effects. Unfortunately, eupafolin is characterized by poor water solubility and skin penetration, which limits its clinical applications. To address these issues, we successfully synthesized a eupafolin nanoparticle delivery system (ENDS). Our findings showed that ENDS could overcome the physicochemical drawbacks of raw eupafolin with respect to water solubility and skin penetration, through reduction of particle size and formation of an amorphous state with hydrogen bonding. Moreover, ENDS was superior to raw eupafolin in attenuating PM-induced oxidative stress and inflammation in HaCaT keratinocytes, by mediating the antioxidant pathway (decreased reactive oxygen species production and nicotinamide adenine dinucleotide phosphate oxidase activity) and anti-inflammation pathway (decreased cyclooxygenase-2 expression and prostaglandin E2 production through downregulation of mitogen-activated protein kinase and nuclear factor-κB signaling). In summary, ENDS shows better antioxidant and anti-inflammatory activities than raw eupafolin through improvement of water solubility and skin penetration. Therefore, ENDS may potentially be used as a medicinal drug and/or cosmeceutical product to prevent PM-induced skin inflammation.